Expression and Regulation of Deubiquitinase-Resistant, Unanchored Ubiquitin Chains in Drosophila. - Blount, J.R.; Libohova, K.; Marsh, G.B.; Sutton, J.R.; Todi, S.V. (Scientific reports, 2018)
The modifier protein, ubiquitin (Ub) regulates various cellular pathways by controlling the fate of substrates to which it is conjugated. Ub moieties are also conjugated to each other, forming chains of various topologies. In cells, poly-Ub is attached to proteins and also exists in unanchored form. Accumulation of unanchored poly-Ub is thought to be harmful and quickly dispersed through dismantling by deubiquitinases (DUBs). We wondered whether disassembly by DUBs is necessary to control unanchored Ub chains in vivo. We generated Drosophila melanogaster lines that express Ub chains non-cleavable into mono-Ub by DUBs. These chains are rapidly modified with different linkages and represent various types of unanchored species. We found that unanchored poly-Ub is not devastating in Drosophila, under normal conditions or during stress. The DUB-resistant, free Ub chains are degraded by the proteasome, at least in part through the assistance of VCP and its cofactor, p47. Also, unanchored poly-Ub that cannot be cleaved by DUBs can be conjugated en bloc, in vivo. Our results indicate that unanchored poly-Ub species need not be intrinsically toxic; they can be controlled independently of DUB-based disassembly by being degraded, or through conjugation onto other proteins.